2014
DOI: 10.3805/eands.7.30
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Exacerbated Infantile Spasms and Induced Novel Complex Partial Seizures in an Infant with Non-ketotic Hyperglycinemia

Abstract: A male infant who presented with neonatal asphyxia began to exhibit infantile spasms at three months of age. His seizures were refractory to conventional antiepileptic drugs including valproic acid, pyridoxal phosphate, zonisamide, clonazepam and adrenocorticotrophic hormone (ACTH)-Zn. Immediately following re-administration of valproic acid, infantile spasms were exacerbated and novel complex partial seizures with oral automatism and pedaling behaviors appeared. An electroencephalogram showed more severe hyps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It is possible that resolution of spasms is a spontaneous remission due to increasing age of the patient, however, it is plausible to claim that it is related to discontinuation of VPA for the following 2 reasons; first, the spasms in this patient is symptomatic secondary to old traumatic brain injury which makes the spontaneous resolution less likely and, second, the time lock of cessation of spasms immediately post discontinuation of the drug. During the literature review for infantile spasms exacerbated by valproic acid, I identified one reported case by Itonaga et al 8 In this case, the spasms were exacerbated after the valproic acid administration. As per the authors, it induced a novel complex partial seizure, suggesting that the patient had distinctive clinical seizures due to non-ketotic hyperglycinemia.…”
Section: Disclosurementioning
confidence: 99%
“…It is possible that resolution of spasms is a spontaneous remission due to increasing age of the patient, however, it is plausible to claim that it is related to discontinuation of VPA for the following 2 reasons; first, the spasms in this patient is symptomatic secondary to old traumatic brain injury which makes the spontaneous resolution less likely and, second, the time lock of cessation of spasms immediately post discontinuation of the drug. During the literature review for infantile spasms exacerbated by valproic acid, I identified one reported case by Itonaga et al 8 In this case, the spasms were exacerbated after the valproic acid administration. As per the authors, it induced a novel complex partial seizure, suggesting that the patient had distinctive clinical seizures due to non-ketotic hyperglycinemia.…”
Section: Disclosurementioning
confidence: 99%